Friendship and Knowledge in Evagrius of Pontus - Gerdon, Ian (Cistercian studies quarterly, 2019)
The article focuses on monk Evagrius of Pontus who has place in history of Christian monasticism and mentions discussions of ancient Christian friendship. Topics discussed include scholarship of Christians who used language and themes associated with friendship, friendship focused on monastic tradition and examination of Evagrius's discussions of friendship.